Substituting trust by technology: A comparative study - Johanna Rath (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2020)
This study contrasts different effects of applying blockchain technology on a social norm of trust and individual behaviour. The advanced technological features of blockchain could either complete contractual information and prevent coordination failures by substituting the need for trust or allow for some degree of incompleteness in information and favour a reciprocal mechanism of trust to solve for inefficiencies arising out of it. Either way, incomplete information is a necessary condition for the emergence of social norms of trust and reciprocity; hence a change in the completion of contractual information influences the institutional setting that market mechanisms are embedded in. One evolutionary process drives both, the degree of information available and behavioural traits within the society. Technology is neutral, but the way it is applied has different consequences on the institutional setting and thus favours different individual behavioural traits. Blockchain technology might either substitute or complement the need for trust.
Keywords: 330; trust; incomplete contracts; social norms; coordination failure